ANTIHYPERLIPIDEMIA ACTIVITY AND MECHANISM TEST OF CASHEW NUT SHELL EXTRACT IN MALE WISTAR RAT INDUCED BY HIGH-CHOLESTEROL FOODS - Rahmi, Era
Hyperlipidemia is a condition when blood cholesterol (lipids) are high. Nutshell is a waste of cashew nuts product which known contain phytosterols that can lower blood lipids. The study aim to determine cashew nut shell extract mechanism of action as antihyperlipidemic agent with parameters such as total cholesterol and histology of rat aorta. This study used male Wistar rats, with two methods: induction of hyperlipidemia and inhibition of cholesterol absorption method. In induction of hyperlipidemia, animals were induced using high cholesterol foods and induction agent (cholesterol, cholic acid, and propylthiouracil), after that were treated using simvastatin and cashew nut shell extract. Total cholesterol value was measured periodically after therapy. After that, the animals were dissected and aorta was isolated to examine the histology of aorta using hematoxylin-eosin staining. In inhibition cholesterol absorption method, rats were given PTU 9 mg kg bw orally for 7 days, then on the day 8, rats were given ezetimibe and extract orally. After that, all the animals were induced with exogenous cholesterol 400 mg/kg bw. Cholesterol leeel in the serum and feces were measured as well as to see the effects of inhibition of cholesterol absorption. All data were analyzed with ANOVA. For hyperlipidemia induction method, lowdose extract and high-dose extract different significantly compared to the control group (p <0.05) respectively around 118.86 ± 46.35 mg /dL and 98.8 ± 37.49 mg dL after 8 weeks of therapy. Triglyceride levels of a low-dose extract and a highdose extract was significantly lower compared to group (p <0.05) respectively by 59.29 ± 13,02 mg/dL and 57.4 19.55 mg/dL. Atherogenic index of plasma (IAP) values of low-dose extract and high dose extract was significantly different compared to the control group (p <0.05) respectively 0.48 ± 0.25 and 0.53 ± 0.20. Histology of rats aorta for low-dose extract, and high-dose extract was significantly different in thickness compared to thé control group (p <0.05) respectively 16,20um ± 54.18 and 67.78 ± 15,14grn. In the inhibition of cholesterol absorption method, cashew nut shell extract at dose of 250mg/kg bw and at dose of 500 mg/kg bw inhibited the increase of total blood cholesterol within one hour after induction and significantly different compared to the control group respectively 30.24% and 34.14%. However, only extract 500mg /kg bw can increase the excretion of total cholesterol in feces collected after 24 hours (68.64%) of cholesterol administration significantly. In conclusion, n-hexane extract cashew nut shell 500mg/kg bw have antihyperlipidemia effects, one of them is inhibition of cholesterol absorption mechanism.